Design aspects of the feed boxes of the Super-FRS Local Cryogenics System. Issue 1 (1st May 2022) - Polinski, J; Chadaj, D; Chorowski, M; Iluk, A; Kollmus, H; Pachnik, L; Simon, H; Wamers, F; Winkler, M; Xiang, Y
Abstract: The Super-FRS is an electromagnetic separator and spectrometer designed for the production and selection of highly energetic and intense exotic heavy-ion beams. It is part of the Facility for Antiproton and Ion Research (FAIR) particle accelerator currently under construction at GSI, Darmstadt, Germany. The Super-FRS will feature in total 63 superconducting magnet cryostats: 27 dipoles, 35 multiplets (7 short and 28 long), and the GLAD experiment magnet. The Super-FRS Local Cryogenics will distribute and feed cold helium from the central cryogenic plant "CRYO2" to the magnet cryostats. Daisy-chain like arrays of feed and end boxes are connected via transfer line pieces. Each single magnet cryostat is supplied by one feed box via a jumper connection. The dipole, short- and long multiplets require different helium mass streams at different operation modes. Moreover, the Local Cryogenics system must follow the Super-FRS curvature and irregular pattern of cryostat locations. In order to simplify the production process, lower the risk of technical mistakes, and increase the flexibility of the installation sequence during the conceptual design project phase an effort was made to develop a uniform construction of the feed boxes for all cryostat types. The paper provides the description of the Super-FRS Local Cryogenics system and the process requirements for all cryostat types in all possible operation modes. The Super-FRS feed box flow scheme and features that allow for unification of its design for all cryostat types are also presented.